Objectives of veil for Muslim woman and removing suspicion from benefits in the light of Quran and Sunnah: اهداف الحجاب للمرأة المسلمة وازالة الشکوک عن استفاداتها فی ضوء القرآن والسنة - Khan, Dr. Hafiz Muhammad; Mushtaque, Sana; Parveen, Alia (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
This paper takes a fresh look at the topic of ‘Veil’ in Islam. It synthesizes the options of different Muslim scholars on the topic. Opinions in favour and against ‘Veil’ have been academically dealt with in a critical analytical approach. It aims at bringing the subject into fresh discussion in order to apprise desirous Muslim women to confidently apply the decorum of Veil accordingly. Muslim scholars are divided into three different groups on the object of veil. The first group does not recognise it as an essential part of Muslim behaviour. They consider Veil more to be spiritual. The second one accepts it moderately and allows face, palms and dresses to be exposed for asphaltic sense. The third school of thought allows no such concession in the record. There is strict adherence to the veil of the face, body dress even the voice of women is considered related to it. In a Muslim society, women are obligated to follow of God as much as men. Veil order are based on the texture guidance of Quran and Sunnah. In the Islamic Reviling at Veil has a special identity and a special place. This paper highlights the same to show how important this area of study is.